In vivo tau pathology is associated with synaptic loss and altered synaptic function - Coomans, Emma M.; Schoonhoven, Deborah N.; Tuncel, Hayel; Verfaillie, Sander C. J.; Wolters, Emma E.; Boellaard, Ronald; Ossenkoppele, Rik; den Braber, Anouk; Scheper, Wiep; Schober, Patrick; Sweeney, Steven P.; Ryan, J. Michael; et al. (Alzheimer's research & therapy, 2021)
Background The mechanism of synaptic loss in Alzheimer’s disease is poorly understood and may be associated with tau pathology. In this combined positron emission tomography (PET) and magnetoencephalography (MEG) study, we aimed to investigate spatial associations between regional tau pathology ([ 18 F]flortaucipir PET), synaptic density (synaptic vesicle 2A [ 11 C]UCB-J PET) and synaptic function (MEG) in Alzheimer’s disease. Methods Seven amyloid-positive Alzheimer’s disease subjects from the Amsterdam Dementia Cohort underwent dynamic 130-min [ 18 F]flortaucipir PET, dynamic 60-min [ 11 C]UCB-J PET with arterial sampling and 2 × 5-min resting-state MEG measurement. [ 18 F]flortaucipir- and [ 11 C]UCB-J-specific binding (binding potential, BP ND ) and MEG spectral measures (relative delta, theta and alpha power; broadband power; and peak frequency) were assessed in cortical brain regions of interest. Associations between regional [ 18 F]flortaucipir BP ND , [ 11 C]UCB-J BP ND and MEG spectral measures were assessed using Spearman correlations and generalized estimating equation models. Results Across subjects, higher regional [ 18 F]flortaucipir uptake was associated with lower [ 11 C]UCB-J uptake. Within subjects, the association between [ 11 C]UCB-J and [ 18 F]flortaucipir depended on within-subject neocortical tau load; negative associations were observed when neocortical tau load was high, gradually changing into opposite patterns with decreasing neocortical tau burden. Both higher [ 18 F]flortaucipir and lower [ 11 C]UCB-J uptake were associated with altered synaptic function, indicative of slowing of oscillatory activity, most pronounced in the occipital lobe. Conclusions These results indicate that in Alzheimer’s disease, tau pathology is closely associated with reduced synaptic density and synaptic dysfunction.